Modern Approaches to Achieving Control over Common Health Disorders in Infants: the Effectiveness of Extensively Hydrolyzed and Amino Acid Formulas - Elena A. Vishneva; Darya S. Chemakina; Yulia G. Levina; Kamilla E. Efendieva; Vera G. Kalugina; Anna A. Alekseeva; Liliya R. Selimzyanova; Elena V. Kaitukova; Vladimir A. Barannik (Педиатрическая фармакология)
Proper nutrition of the mother and baby is the most important condition for the development and health of the child. It is the first 1000 days of a child’s life that are critical for neuroontogenesis, the formation of further abilities to acquire and improve various skills, and to learn successfully. It is the first 1000 days of a child’s life that are critical for neuroontogenesis, the formation of further abilities to acquire and improve various skills, and to learn successfully. Breast milk is the “gold standard” of nutrition for all newborns, including children with functional digestive disorders and food allergies. Supporting and promoting adherence to breastfeeding in the first 6 months of a child’s life are the most important tasks for all medical professionals providing medical care to children. The most common pathological conditions among children of the first year of life are functional digestive disorders and manifestations of food allergies, in which diet therapy is the main type of treatment. In situations where breast milk is not available to such an infant, it is important to make the right choice of formula. Modern formulas for artificial feeding of newborns and infants have a number of useful properties due to the features of the composition, which bring them as close as possible to breast milk, specially designed to provide adequate nutrition and simultaneously perform therapeutic tasks.